ANALISIS HASIL BELAJAR DENGAN METODE PEMBELAJARAN DARING SISWA KELAS IV MADRASAH IBTIDAIYAH AL-GAOTSIYAH KAMAL RAYA JAKARTA BARAT - Anisah Fitri; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
Learning with the online method is a method used during the Covid-19 pandemic, teachers are needed to be able to learn effectively online at home, and teachers must be creative in implementing learning so that student learning outcomes are achieved well. A person can be declared successful in learning if he can show a change in thinking abilities, skills, and attitudes. Changes in learning outcomes can be observed, proven, and measured in the abilities and achievements experienced by students as a result of learning experiences built with the learning process. One of the elementary schools that has experienced this online learning is one of the elementary schools in the author's environment that conducts online learning, Madrasah Ibtidaiyah Al-Gaotsiyah Kamal Raya, West Jakarta. One of the elementary schools in the author's environment also carries out online learning. The author is interested in knowing the learning outcomes of Madrasah Ibtidaiyah Al-Gaotsiyah Kamal Raya West Jakarta when used in implementing online learning. This study aims to determine the results of online learning methods, as well as follow online learning. The inhibiting factors of online learning, and how to improve student learning outcomes in the process of online learning outcomes for fourth grade students of Madrasah Ibtidaiyah Al-Gaotsiyah Kamal Raya, West Jakarta. The method used in this study is a qualitative approach and uses a descriptive type of research. The results showed: (1) The results of online learning methods in fourth grade students of Madrasah Ibtidaiyah Al-Gaotsiyah decreased learning outcomes from the previous face-to-face learning, because the value of the cognitive, affective, and psychomotor domains and the value of student report cards decreased. (2) The inhibiting factors in using online learning methods for fourth grade students of Madrasah Ibtidaiyah Al-Gaotsiyah are the quota and network factors, and other factors such as unsupportive environmental conditions, the presence of students who do not have personal cellphones and factors from the students themselves are less enthusiastic in participating in online learning. (3) To improve student learning outcomes in the process of online learning outcomes for fourth grade students of Madrasah Ibtidaiyah Al-Gaotsiyah, the teacher must add several applications in delivering learning materials and apply blended learning methods.